The Impact of Gender on Political Perception: A Reception Study of the July 2023 Spanish Election Campaign (Communication & Society, 2025)
The Spanish general election held on July 23, 2023, was significantly influenced by the discourse on feminism and gender-based violence, issues that all the political parties were determined to address either directly or indirectly. This research paper explores the electorate’s reception of the feminist agenda, evaluating the extent to which the gender perspective is integrated into political discourse and resonates with the general public and investigating the gender-specific perceptions and biases that influence their assessment of political candidates. The responses to a survey administered between July 19 and 21, 2023 to 1,590 Spanish residents aged 18 and above, demographically weighted by gender, age, and geographical location, reflect the profound influence of gender on electoral perceptions and reveal nuanced differences in the evaluation of conservative candidates according to respondents’ gender. Notably, the analysis highlights the critical role of women in moderating the advance of conservative and far-right political narratives. This study contributes to the broader discourse on gender politics by underscoring the complex interplay between feminist policies and political perceptions within the context of the 2023 Spanish general election.